IS THERE A PRESCRIBED LENGTH FOR A DECLARATION BY AN APPLICANT AND/OR A PLEA BY A RESPONDENT IN RULE 43(2) AND (3) APPLICATIONS? - Mothokoa Mamashela (Obiter, 2023)
This case note investigates the interpretation of Rule 43(2) and (3) of the Uniform Rules of Court. It determines whether there is a prescribed length for such applications and pleas under the Rules. It takes a historical perspective, tracing two contradictory views in case law and considers how the courts have interpreted these two views in their different judgments. Some courts have interpreted the Rules strictly; they have held that such applications and pleas should be brief, succinct and to the point. Others have disagreed with the strict interpretation and allowed prolixity. The input of the legal fraternity (the Cape Bar and the Law Society of South Africa) on the shortcomings of the Rules, and how they could be amended, is discussed. The ruling of the full bench of the Gauteng Local Division of the High Court has answered the question. It has held that there is no one-size-fits-all approach under the rule. Each case must be determined according to its own merits. Simple cases may be disposed of expeditiously, but complicated cases should not be struck off the roll because of prolixity.